Optical genome mapping: Unraveling complex variations and enabling precise diagnosis in dystrophinopathy - Jiahui Mai; Jing Duan; Xiaoyu Chen; Liqin Liu; Dachao Liang; Tao Fu; Gang Lu; Wai Yee Chan; Xufeng Luo; Feiqiu Wen; Jianxiang Liao; Zhuo Li; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Approximately 7% of individuals with dystrophinopathy remain undiagnosed at the genetic level using conventional genetic tests like multiplex ligation‐dependent probe amplification (MLPA) and next‐generation sequencing (NGS). We used the optical genome mapping (OGM) technology to detect and analyze uncommon mutations or structural variations (SVs) within the DMD gene, thus contributing to more precise clinical diagnoses. Methods We herein included eight patients with dystrophinopathy (six males and two females) in whom pathogenic variants of the DMD gene could not be accurately identified using MLPA and NGS. Clinical data were collected for all patients and genetic testing was performed using OGM. Results Conventional methods (MLPA and NGS) failed to detect pathogenic mutations in six out of eight individuals (four males and two females). OGM testing uncovered rare mutations in the DMD gene in four patients, including a pericentric inversion in chromosome X (one male), a complex rearrangement (one male), and two X–autosome translocations (two females). No mutations were detected in the remaining two male patients. OGM also accurately mapped balanced X–autosome translocations in female patients, defining chromosomal breakpoints. In the other two male patients in whom MLPA suggested non‐contiguous exon duplications or deletions in the DMD gene, OGM characterized one case as a complex rearrangement and the other as a deletion within the DMD gene. Interpretation OGM is a valuable diagnostic tool for dystrophinopathy patients with negative results from conventional genetic tests. It can effectively elucidate complex SVs and pinpoint breakpoints in X–autosomal translocations in female patients, facilitating prompt and appropriate interventions.